Anti-fog and anti-frost coatings with low coefficient of friction
The coating composition, featuring urethane resins and water-absorbent polymers, addresses the sticky surface issue of existing anti-fog coatings by providing a smooth, permanent anti-fog and anti-frost solution that improves handling and packaging.
Patent Information
- Application Number
- JP2024551991
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-09-13
- Filing Date
- 2023-09-12
- Publication Date
- 2025-04-30
AI Technical Summary
Existing anti-fog coatings often have a sticky surface feel, leading to handling and packaging issues, and they may not provide both permanent anti-fog and anti-frost properties simultaneously.
A coating composition comprising urethane resins obtained by reacting isocyanate-reactive compounds with multiepoxide functionality with isocyanate, combined with water-absorbent polymers and curing agents, which forms a clear, smooth, and permanent anti-fog and anti-frost coating when heat-cured.
The coating achieves long-lasting antifog and anti-frost properties with a smooth surface feel, enhancing handling, cleaning, and packaging ease while providing resistance to microparticle damage.
Smart Images

Figure 2025513688000001 
Figure 2025513688000002 
Figure 2025513688000003
Abstract
Description
[Technical field]
[0001] Related Applications This application claims priority to and the entire benefit of U.S. Provisional Patent Application Serial No. 63 / 406,030, filed September 13, 2022, for Anti-Fog and Anti-Frost Coatings Having a Low Coefficient of Friction, the entire disclosure of which is incorporated herein by reference.
[0002] The present disclosure relates to compositions for forming coatings having anti-fog and / or anti-frost properties, articles including such coatings, and methods for making the coatings and / or articles. [Background technology]
[0003] Anti-fog properties are desirable in applications such as ophthalmic lenses and sunglasses; safety, military, and sports eyewear and accessories; automotive, transportation, architectural, and greenhouse glazing; industrial, point-of-sale, and electronic displays; mirrors; solar panels; and other articles. Frost resistance is advantageous in low temperature applications such as freezer doors, sportswear, etc. In many cases, the dual function of anti-fog and anti-frost in the same coating is desired.
[0004] Fogging occurs when water vapor from the surrounding air condenses on an article to form small water droplets. This occurs when the article is at a temperature lower than the ambient temperature, thereby cooling the surrounding air below its dew point. Current anti-fog coatings are typically hydrophilic in nature. Surfactants are used in coating formulations to increase the surface energy of the cured coating, allowing the droplets to sheet out across the surface of the substrate (i.e., wet the surface of the substrate) rather than forming spherical droplets on the substrate. The resulting water sheeting effect minimizes light scattering, improving visibility.
[0005] Frost forms when the surface of an article is below the freezing point of water. Water condensed in this scenario freezes on the article. Often, it is desirable for a coating to have both anti-fog and anti-frost properties. For example, in an article such as ski goggles, heat emitted by the skier's body causes fogging on the inside of the ski goggles. Therefore, anti-fog is important on the inside of the ski goggles. However, the outside of the ski goggles is exposed to a cold, snowy environment and therefore requires anti-frost properties. Therefore, a coating that can function as both an anti-fog and anti-frost is important.
[0006] To achieve long-lasting or permanent anti-fog properties, anti-fog coatings are typically formulated with high amounts of surfactants in combination with a hydrophilic network. Such high surfactant loadings and hydrophilic networks often result in cured coatings that are less smooth to the touch. As a result, articles coated with anti-fog paints are less easy to handle and clean. High surfactant loadings also make the coatings more susceptible to scratches when packaged in low-quality bags.
[0007] Resistance to fogging and resistance to surface damage by particulates are essential criteria for eyewear to be considered as personal protective equipment. Furthermore, personal protective eyewear should ideally pass and be certified according to the European standard EN 166 (e.g. EN 166, revised 2001). EN 166 includes several tests for various safety requirements, namely stability at high temperatures, resistance to UV rays, corrosion, ignition, fogging, and surface damage by large / particulate particles. The test methods included in the EN 166 certification are EN 167, which contains optical test methods, and EN 168, which contains non-optical test methods. Resistance to fogging of lenses (called "N-mark") and resistance to surface damage by particulates (called "K-mark") are included in EN 168. Thus, eyewear with a cured coating that is resistant to fogging and passes the tests specified in EN 168 is considered to have the EN 166 N-mark. Similarly, eyeglasses having a cured coating that passes the EN 168 test for resistance to surface damage by particulates are considered to have the EN 166 K mark. Summary of the Invention
[0008] The present disclosure provides a coating composition comprising a urethane resin, a water-absorbing polymer, and a curing agent. The urethane resin is obtained by the reaction of an isocyanate reactive compound having multi-epoxide functionality with an isocyanate. When applied to a substrate and thermally cured, the coating composition forms a clear, smooth coating with durable anti-fog properties.
[0009] Further described in the present disclosure is an article having a substrate and a transparent, smooth and durable anti-fog coating applied thereon. The coating is formed from a coating composition including a urethane resin, a water-absorbing polymer, a curing agent, a dispersant, and a solvent. The urethane resin is the reaction product of an isocyanate-reactive compound having multiple epoxide functionality and an isocyanate.
[0010] In some embodiments of the present disclosure, the coating composition, when applied to a substrate and heat cured, forms a clear, smooth coating that has durable anti-fog as well as frost resistance. The present disclosure also describes an article comprising the clear, smooth coating applied onto a substrate that has durable anti-fog and frost resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] This disclosure describes a coating composition. The multi-component composition includes a urethane resin, a water-absorbing polymer, and a curing agent. The urethane resin is obtained by the reaction of an isocyanate-reactive compound having multiple epoxide functionality with an isocyanate. When applied to a substrate and thermally cured, the coating composition forms a clear, smooth coating with durable anti-fog properties. The coating composition may further include a dispersant and a solvent.
[0012] Further described in this disclosure is an article having a substrate and a transparent, smooth, anti-fog coating applied onto the substrate, the coating being formed from the coating composition disclosed herein.
[0013] Due to the inherent nature of hydrophilic, surfactant-rich systems, anti-fog coatings tend to have a grippy / sticky surface feel. As a result, anti-fog coatings can adhere to packaging materials such as high density polyethylene (HDPE), low density polyethylene (LDPE), cast polypropylene (CPP), chlorinated polyethylene (CPE), polypropylene (PP), and polyethylene (PE), leaving scratches on the coated article. Coated articles with smooth (non-sticky / non-grabable) surfaces are easier to insert and remove from various packages made from such materials. Also, since anti-fog and anti-frost coatings are often used on eyeglasses, end users often dislike the grippy feel when wiping lenses or goggles with a cloth. Thus, a smooth surface feel of anti-fog and anti-frost coatings is highly desirable.
[0014] The coating composition of the present disclosure provides articles such as eyeglasses with a coating that has long-lasting anti-fog and / or anti-frost properties and a smooth / smooth surface feel, achieved by the combination of a water-absorbing polymer and a hydrophilic network of a urethane resin with crosslinked epoxide groups. The coating facilitates handling, cleaning, and packaging. Additionally, the coating can provide the article with resistance to damage caused by particulates. Urethane Resin
[0015] As described above, the coating composition comprises a urethane resin obtained by reacting an isocyanate-reactive compound having multiple epoxide functionality with an isocyanate. When the coating composition is applied to an article, the resulting network provides long term adhesion to the substrate.
[0016] The isocyanate-reactive compound having multiple epoxide functionality contains at least two epoxide groups. In accordance with the present disclosure, the isocyanate-reactive compound having multiple epoxide functionality may contain three or more epoxide groups. The epoxide groups further contribute to the hydrophilicity upon curing and thus the durable anti-fog properties of the coating.
[0017] The isocyanate-reactive compound having multiple epoxide functionality includes at least one isocyanate-reactive group. In accordance with the present disclosure, the isocyanate-reactive compound having multiple epoxide functionality may include at least one hydroxyl group as an isocyanate-reactive group.
[0018] In accordance with the present disclosure, the isocyanate-reactive compound having multiple epoxide functionality may be ethoxylated and / or propoxylated. In some embodiments of the present disclosure, optimal anti-fog properties are achieved with an isocyanate-reactive compound having multiple epoxide functionality that includes at least one ethyleneoxy and / or propyleneoxy chain and at least one hydroxyl group.
[0019] The isocyanate-reactive compounds having multi-epoxide functionality may or may not contain silicon atoms.
[0020] Suitable isocyanate-reactive compounds having multiple epoxide functionality which may be used include aromatic polyepoxides, aliphatic polyepoxides, particularly polyfunctional aliphatic polyepoxides, glycerol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitol polyglycidyl ether, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, phenoxy(ethylene oxide) 5 glycidyl ether, and lauryloxy(ethylene oxide) 15 glycidyl ethers, or combinations thereof. Examples of commercially available polyfunctional aliphatic polyepoxides include: aliphatic polyepoxide (Denacol EX-1610), glycerol polyglycidyl ether (Denacol EX-313), polyglycerol polyglycidyl ether (Denacol EX-512 and EX-521), sorbitol polyglycidyl ether (Denacol EX-614B), ethylene glycol diglycidyl ether (Denacol EX-810 and EX-811), diethylene glycol diglycidyl ether (Denacol EX-850 and EX-851), polyethylene glycol diglycidyl ether (Denacol EX-821, EX-830, EX-832, EX-841 and EX-861), polypropylene glycol diglycidyl ether (Denacol EX-920), phenoxy(ethylene oxide) 5 glycidyl ether (Denacol EX-145), and lauryloxy(ethylene oxide). 15 glycidyl ether (Denacol EX-171). All of the above commercially available products are manufactured by Nagase ChemteX Corporation. Similar resins are available from other companies.
[0021] The urethane resins disclosed herein may be present in the coating composition in an amount from 1 to 95 wt%, including, for example, 20 to 90 wt%, 35 to 85 wt%, and 50 to 80 wt%, based on the total solids content of the coating composition.
[0022] The isocyanate-reactive compounds having multi-epoxide functionality disclosed herein may be present in the coating composition in an amount from 0.5 to 90 wt%, including, for example, 8 to 70 wt%, 8 to 65 wt%, 10 to 60 wt%, 20 to 50 wt%, and 30 to 40 wt%, based on the total solids content of the coating composition.
[0023] The isocyanate may be a silicon-containing isocyanate, a non-silicon-containing isocyanate, or a combination thereof. Silicon-containing isocyanates include NCO(R)Si(OR 1 )3, NCO(R)Si(OR 1 )2R 3 , NCO(R)Si(OR 1 )(R 3 )2(R=(CH2) n , n = 1 to 6, R 1 =CH3 or C2H5, and R 3 =C x E 2x+1, x=1-4), or combinations thereof. In some embodiments of the present disclosure, the silicon-containing isocyanate may include polyisocyanates (i.e., isocyanates with an isocyanate functionality greater than 1). Suitable silicon-containing isocyanates that may be used include, but are not limited to, 3-isocyanatopropyltriethoxysilane, 3-isocyanatopropyltrimethoxysilane, 2-isocyanatoethyltrimethoxysilane, 2-isocyanatoethyltriethoxysilane, 3-isocyanatopropylmethyldimethoxysilane, 2-isocyanatoethylmethyldimethoxysilane, 3-isocyanatopropylmethyldiethoxysilane, 2-isocyanatoethylmethyldiethoxysilane, 4-isocyanatobutyltrimethoxysilane, 4-isocyanatobutyltriethoxysilane, 5-isocyanatopentyltrimethoxysilane, 5-isocyanatopentyltriethoxysilane, 6-isocyanatohexyltrimethoxysilane, 6-isocyanatohexyltriethoxysilane, or combinations thereof.
[0024] According to the present disclosure, at least one silicon-containing isocyanate may be a reactive isocyanate alkoxysilane.In such an embodiment, the alkoxy group of the urethane resin obtained by the reaction of the isocyanate-reactive compound having multiple epoxide functionality with the reactive isocyanate alkoxysilane may be further hydrolyzed by, for example, water and acid.
[0025] As mentioned above, the isocyanate may include a silicon-free isocyanate. The silicon-free isocyanate may include a polyisocyanate (i.e., an isocyanate having an isocyanate functionality greater than 1). In some embodiments of the present disclosure, aliphatic polyisocyanates (including, but not limited to, aliphatic diisocyanates and aliphatic triisocyanates) are preferred because they have better light stability than aromatic polyisocyanates. Suitable silicon-free isocyanates having an isocyanate functionality greater than 1 that may be used include, but are not limited to, isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), xylylene diisocyanate (XDI), toluene diisocyanate (TDI), diphenylmethane diisocyanate, HDI biuret, diisocyanates derived from the above isocyanates, or combinations thereof. Examples of such commercially available non-silicon-containing polyisocyanates include Desmodur I, Desmodur N75, and Desmodur W. In some embodiments of the present disclosure, the non-silicon-containing isocyanates include monoisocyanates (i.e., isocyanates having an isocyanate functionality of 1).
[0026] The isocyanates disclosed herein may be present in the coating composition in an amount from 0.1 to 40 wt%, including, for example, 10 to 37 wt%, 20 to 33 wt%, and 25 to 30 wt%, based on the total solids content of the coating composition. Water-absorbent polymer
[0027] As mentioned above, the coating composition includes a water-absorbing polymer that absorbs condensed water that forms on the surface of the cured coating, further enhancing the durable anti-fog properties. The water-absorbing polymer also enhances the frost resistance.
[0028] In accordance with the present disclosure, the water-absorbing polymer may include, but is not limited to, polyvinylpyrrolidone, poly(vinylpyrrolidone-co-vinyl acetate), poly(vinylpyrrolidone-co-ethyl acrylate), poly(vinylpyrrolidone-co-vinyl chloride), polyvinyl alcohol, sulfonic acid esters, polyacrylic acid, or combinations thereof.
[0029] The water-absorbing polymers disclosed herein may be present in the coating composition in an amount of from 0.01 to 50 wt%, including, for example, from 0.01 to 40 wt%, from 5 to 38 wt%, and from 20 to 35 wt%, based on the total solids content of the coating composition. Hardener
[0030] As mentioned above, the coating composition includes a curing agent. The curing agent can be any material that causes crosslinking of the isocyanate-reactive compound with multi-epoxide functionality. In accordance with the present disclosure, the curing agent can be an amine, an amine salt, or a combination thereof, including, for example, aliphatic / aromatic / modified amines, tertiary or secondary amines, imidazoles, polymercaptans, and the like. Examples of suitable specific curing agents that can be used include, but are not limited to, Three Bond 2000 series (2103, 2163, 2162F, 2163C, 2086B, and the like), tris-(dimethylaminomethyl)phenol tri(2-ethylhexoate), tris-(dimethylaminomethyl)phenol, diazabicyclo-undecene, boron trifluoride amine complexes, or combinations thereof. Lewis acid-base adducts such as boron trifluoride amine complexes can also be used as curing agents.
[0031] The curing agents disclosed herein may be present in the coating composition in an amount of from 0.1 to 2 wt %, including, for example, from 0.3 to 1.5 wt %, from 0.5 to 1 wt %, and from 0.6 to 0.7 wt %, based on the total solids content of the coating composition. solvent
[0032] The coating composition may include a solvent. The solvent may include one or more solvents compatible with the urethane resin, such as water, organic solvents, and combinations thereof. The organic solvent may be selected to provide good solubility of the isocyanate-reactive compound with multiple epoxide functionality, the isocyanate, and the water-absorbing polymer. Suitable organic solvents that may be used include, but are not limited to, ketones such as methyl ethyl ketone, methyl isobutyl ketone, diacetone alcohol, 3,3-dimethyl-2-butanone, and pentanedione; esters; glycol esters; primary, secondary, and tertiary alcohols; polar aprotic solvents such as acetonitrile, N-methyl-2-pyrrolidone, dimethylformamide, dimethylsulfoxide, and ethers such as 1,2-dimethoxyethane and PM glycol ether.
[0033] The solvents disclosed herein may be present in the coating composition in an amount such that the total solids content of the coating composition is from 5 to 75 wt%, including, for example, from 10 to 45 wt%, from 15 to 40 wt%, and from 20 to 35 wt%. Dispersants
[0034] The coating composition may further comprise a dispersant. The dispersant can enhance the solubility of other polymers, such as urethane resin or water-absorbing polymer, especially in aqueous-organic solvent mixture. The enhanced solubility of components allows them to be included in the coating composition in a larger amount while maintaining good stability and applicability of the coating composition. In some embodiments of the present disclosure, the dispersant allows the inclusion of a larger amount of water-absorbing polymer in the coating composition, which in turn improves the anti-fog and / or anti-frost properties of the coating formed.
[0035] According to the present disclosure, the dispersant may be a polymeric dispersant having hydrophilic and hydrophobic segments.Suitable commercially available dispersants that may be used include, but are not limited to, Disperbyk 2013, Disperbyk 161, Solsperse W100, Solsperse W150, Solsperse W430, or combinations thereof.
[0036] The dispersants disclosed herein may be present in the coating composition in an amount of from 0 to 10 wt%, including, for example, 0.1 to 5 wt%, 0.1 to 1 wt%, and 0.2 to 0.75 wt%, based on the total solids content of the coating composition. Additional Aspects
[0037] The coating composition may further include one or more optional ingredients, as described below. The one or more optional ingredients may be present in the coating composition in an amount of from 0 to 20 wt%, including, for example, from 1 to 10 wt%, from 2 to 8 wt%, and from 3 to 6 wt%, based on the total solids content of the coating composition.
[0038] The coating composition may further comprise a flow modifier, also known in the art as a leveling agent or flow control agent. The flow modifier can help to spread or level the coating composition evenly on the surface of the substrate to provide a substantially uniform contact with the substrate. The flow modifier can be selected from any conventional flow modifier or leveling agent that is compatible with the coating composition and the substrate. Suitable flow modifiers that may be used include, but are not limited to, polyethers, silicones, fluorosurfactants, polyacrylates, silicone polyacrylates such as silicone hexaacrylate, fluorine-modified polyacrylates, or combinations thereof. Examples of commercially available rheology modifiers include BYK 333, BYK 350, BYK 354, BYK 356, BYK 3420, Capstone FS-35, Capstone FS-31, Capstone FS-61, TRITON X-100, X-405, and N-57 from Rohm and Haas; Paint Additive 3, Paint Additive 29, and Paint Additive 57 (silicones) from Dow Corning; SIL WET L-77 and SIL WET L-7600 from Momentive, Inc. (Columbus, Ohio); FLUORAD FC-4430 (fluorosurfactant) from 3M, Inc. (St. Paul, Minn.); and Tegomer from Evonik. E-Si2330, and KF-1002, X-22-3939A, X-22-4741, and KP-301 manufactured by Shin-Etsu Chemical Co., Ltd. The flow modifiers disclosed herein may be present in the coating composition in an amount of from 0 to 20 wt%, including, for example, from 1 to 10 wt%, from 2 to 8 wt%, and from 3 to 6 wt%, based on the total solids content of the coating composition.
[0039] The coating composition may further comprise a non-reactive surfactant. In a haze-generating environment, the non-reactive surfactant will rise quickly to the surface and cause water sheeting, preventing the formation of haze. The non-reactive surfactants are not bonded and do not form part of the network. Instead, they may be bound to the network by weak van der Waals or hydrogen bonds. Suitable non-reactive surfactants that may be used include, but are not limited to, sodium dioctyl sulfosuccinate, sodium bistridecyl sulfosuccinate, sodium dihexyl sulfosuccinate, sodium dicyclohexyl sulfosuccinate, sodium diamyl sulfosuccinate, sodium diisobutyl sulfosuccinate, alkylamine-guanidine polyoxyethanol, or combinations thereof. The non-reactive surfactants disclosed herein may be present in the coating composition in an amount of 0-20% by weight, including, for example, 1-20% by weight, 1-15% by weight, and 6-11% by weight, based on the total solids content of the coating composition.
[0040] The coating composition may further comprise a UV absorber to inhibit the degradation of the substrate material (e.g., aromatic plastics such as polycarbonate) under exposure to UV light or natural weathering. Suitable UV absorbers that may be used include, but are not limited to, 1) 2-hydroxy-benzophenone (BP) derivatives, such as commercially available Chimassorb® 81 and Chimassorb® 90 (both from BASF, Germany); 2) 2-(2-hydroxyphenyl)-benzotriazole (HPBT) derivatives, such as commercially available Tinuvin® 1130, Tinuvin® 384-2, Tinuvin® 928, and Tinuvin® 900 (both from BASF, Germany); 3) 2-hydroxyphenyl-s-triazine (HPT) derivatives, such as commercially available Tinuvin® 400 and Tinuvin® 405 (both from BASF, Germany).
[0041] The coating composition may further include a hindered amine light stabilizer (HALS) for stabilization against the harmful effects of light and weathering. Suitable HALS that may be used include, but are not limited to, derivatives of 2,2,6,6-tetramethylpiperidine. Commercially available examples include Tinuvin® 152 and Tinuvin® 292 (both manufactured by BASF, Germany).
[0042] The coating composition may further include one or more additives to improve the abrasion resistance of the coating, such as metal oxide nanoparticles, and hydrolysis and condensation products of alkoxysiloxanes. Suitable examples of metal oxide nanoparticles include, but are not limited to, silica particles, titania, alumina, zinc oxide, antimony oxide, tin oxide, zirconium oxide, and combinations thereof. The size and concentration of the metal nanoparticles can be selected so that the resulting coating is optically transparent while retaining anti-fog and abrasion resistance. In some embodiments of the present disclosure, the coating composition includes metal oxide nanoparticles having a size in the range of 5 to 50 nm, including 7 to 40 nm, 9 to 30 nm, and 10 to 20 nm.
[0043] The coating composition may further include one or more additives selected from antioxidants, antistatic agents, weathering agents, tint additives, UV stabilizers, antifoaming agents, heat stabilizers, and surface modifiers. Examples of antioxidants include octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and pentaerythrityl tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]. Examples of heat stabilizers include triphenyl phosphite, tris-(2,6-dimethylphenyl)phosphite, tris-(2,4-di-t-butyl-phenyl)phosphite, tris-(mixed mono- and di-nonylphenyl phosphite)phosphite, dimethylbenzene phosphonate, and trimethyl phosphate. Examples of antistatic agents include glycerol monostearate, sodium stearyl sulfonate, and sodium dodecylbenzene sulfonate. Goods
[0044] As mentioned above, an article is described in the present disclosure. The article has a substrate and a transparent and smooth anti-fog coating applied on the substrate. The substrate may be a rigid substrate or a flexible substrate. Suitable substrate materials include, but are not limited to, transparent plastics such as polycarbonate (PC), polarized polycarbonate, polyamide, polyacrylic, polymethyl methacrylate (PMMA), polyvinyl chloride, polybisallyl carbonate, allyl diglycol carbonate (ADC) polymer, polyethylene terephthalate (PET), polyethylene naphthenate, cellulose triacetate (CTA) polymer, cellulose acetate butyrate (CAB) polymer, polyurethane, polyepisulfide, and polythiourethane; various polyolefins, fluorinated polymers, metals, and soda-lime glass, borosilicate glass, and acrylic glass, among other types of glass.
[0045] A transparent, smooth anti-fog coating is formed from the coating composition disclosed herein. The coating composition can be applied to a substrate in any suitable manner, for example, by flow coating, spray coating, curtain coating, dip coating, spin coating, slot die coating, roll coating, and the like, by conventional methods to form a continuous surface film on the substrate. The coating composition is then cured, for example, by exposing the coated substrate to heat, in accordance with a combination of an isocyanate-reactive compound having multiple epoxide functionality and a curing agent. The heat source can be a conventional oven, a convection oven, or an IR oven. In some embodiments of the present disclosure, heat is applied to achieve a temperature of 50-150°C for 10 minutes to 4 hours, including 100-125°C for 10 minutes to 2 hours.
[0046] When the coating composition cures, a hydrophilic polymer network (e.g., a polyether-polyurethane network) is generally formed in the coating. This network further forms an interpenetrating network with the water-absorbing polymer. The combination of the water-absorbing polymer and the polymer network in the coating provides a durable anti-fog property. In some embodiments of the present disclosure, the coating further has anti-frost property in addition to the durable anti-fog property.
[0047] If necessary, the substrate can be subjected to a suitable pretreatment, for example, to enhance the adhesion of the coating composition to the substrate, the substrate can be subjected to a surface treatment and / or coated with a primer, such as an acrylate-based primer (especially for PMMA substrates) and a polyurethane dispersion (PUD)-based primer.
[0048] Examples of articles include, but are not limited to, safety glasses; optical lenses; goggles; face shields; faceplates for helmets; glazing used as building windows and as windshields or windows for automobiles, buses, trains, airplanes, and other transport vehicles; multi-function LED or LCD displays; bathroom mirrors; and shower mirrors and fixtures. Other examples include commercial freezer doors, ice cream freezer doors, and deli cases. According to the present disclosure, the coating formed from the coating composition can be adapted for anti-reflective coating or mirror coating.
[0049] The coating composition can be applied and cured on thin flexible substrates such as PC or PET films, which are then installed or retrofitted by dry or wet lamination onto rigid substrates. The thin flexible substrates with the coating can also be applied to articles requiring anti-fog functionality, such as safety glasses, optical lenses, goggles, face shields, faceplates for helmets, glazing used as windows in buildings, glazing used as windshields or windows in automobiles, buses, trains, airplanes, and other transportation vehicles, multi-function LED and LCD displays, and bathroom and shower mirrors. Coating properties
[0050] When applied to a substrate and cured, the coating composition forms a clear, smooth coating with durable anti-fog properties. In accordance with the present disclosure, "smooth" is defined as having a low coefficient of friction, including less than 0.37, including 0.05-0.35, 0.1-0.29, 0.15-0.25, and 0.18-0.22. In accordance with the present disclosure, the coating can have long-lasting smoothness, meaning that after immersion in deionized water for 7 hours, the coating retains a coefficient of friction of less than 0.37, including 0.05-0.35, 0.1-0.29, 0.15-0.25, and 0.18-0.22.
[0051] In accordance with this disclosure, "durable anti-fog properties" means that no fogging is present for at least 8 seconds when the coated substrate is immersed in water for at least 1 hour (e.g., 1 hour or 2 hours), equilibrated at 25°C and 50% relative humidity for at least 12 hours, and exposed to steam from water at 50°C.
[0052] In accordance with the present disclosure, the coating composition may form a coating having frost-resistant properties. In accordance with the present disclosure, "frost-resistant" means that frost does not form on the coating when the coated substrate is placed at -18°C for 1 hour and then at 20±5°C and a relative humidity of 30-50%.
[0053] According to the present disclosure, the coating composition may form a coating having wipeable anti-fog properties. According to the present disclosure, "wipeable anti-fog properties" means that no fog is present for at least 10 seconds when the coated substrate is wiped with a moist lint-free cleanroom wiper weighing 100 g for 10 cycles with 5 strokes in each cycle and exposed to steam from water at 60°C. According to the present disclosure, the coating composition may form a coating that is free of fog after being wiped for 15 cycles.
[0054] In accordance with the present disclosure, the coating composition is capable of forming a coating that is abrasion resistant to particulates per EN166 / EN168 protocols, where the coating passes the K-mark test. Working Example
[0055] The following examples are merely representative and should not be used to limit the scope of the present disclosure. There are many different alternative designs for the methods and compositions disclosed in the examples. Therefore, the selected examples are primarily used to illustrate the principles of the compositions and methods disclosed herein. General description of the chemicals used [Table 1]
[0056] Example 1 138.4g of Denacol EX-614B (an aliphatic epoxy compound based on sorbitol polyglycidyl ether), 61.58g of Silquest Alink25 (3-isocyanatopropyltriethoxysilane) are weighed into a round bottom flask and mixed until uniform. The mixture is placed in a 70°C water bath. With continued stirring, 0.05g of Fomrez UL-22 catalyst is added. The reaction is allowed to proceed for 2 hours.
[0057] Example 1A 109.8g of Denacol EX-521, 20.52g of Silquest Alink25 (3-isocyanatopropyltriethoxysilane) are weighed into a round bottom flask and mixed until uniform. The mixture is placed in a 70°C water bath. With continued stirring, 0.05g of Fomrez UL-22 catalyst is added. The reaction is allowed to proceed for 2 hours.
[0058] Example 2 To 115.3g of Denacol Ex-614B was added 16.6g of diacetone alcohol and 55.5g of isophorone diisocyanate. The mixture was stirred until homogenous. The mixture was then placed in a 70°C water bath and stirring was continued. 0.05g of Fomrez UL-22 was added to the mixture. After 2 hours of reaction, 51g of PM glycol ether was added. The reaction was continued for another 2 hours.
[0059] Example 34g of polyvinylpyrrolidone K90, 0.08g of Solsperse W100, 76.53g of PM glycol ether were weighed into a container and mixed for 1 hour until a homogeneous mixture was obtained. To this was added 14.8g of the compound obtained in Example 1, followed by 1.25g of Nalco 1034 silica sol with mixing. 0.64g of water, 0.68g of glacial acetic acid, 0.17g of Ancamine K61B, 1.33g of Aerosol OT75, 0.38g of Schercoquat IAS-PG, 0.11g of 10% Byk 333 in PM glycol ether were also added. Mixing was continued for about 12 hours.
[0060] Example 4 4 g of polyvinylpyrrolidone K90, 0.08 g of Solsperse W100, 75.88 g of PM glycol ether were weighed into a container and mixed for 1 hour until a homogeneous mixture was obtained. To this was added 16 g of the compound obtained in Example 1 while mixing. 1.29 g of water, 0.67 g of glacial acetic acid, 0.17 g of Ancamine K61B, 1.33 g of Aerosol OT75, 0.38 g of Schercoquat IAS-PG, 0.2 g of 10% Byk 333 in PM glycol ether were also added. Mixing was continued for about 12 hours.
[0061] Example 5 4.9g of polyvinylpyrrolidone K90, 0.08g of Solsperse W100, 76.38g of PM glycol ether were weighed into a container and mixed for 1 hour until a homogeneous mixture was obtained. To this was added 14.9g of the compound obtained in Example 1 with mixing. 1.2g of water, 0.63g of glacial acetic acid, 0.16g of Ancamine K61B, 1.25g of Aerosol OT75, 0.35g of Schercoquat IAS-PG, 0.15g of 1% Tegomer E-Si2330 in PM glycol ether were also added. Mixing was continued for about 12 hours.
[0062] Example 64.9g of polyvinylpyrrolidone K90, 0.08g of Solsperse W100, 76.48g of PM glycol ether were weighed into a container and mixed for 1 hour until a homogeneous mixture was obtained. To this was added 14.9g of the compound obtained in Example 1 with mixing. 1.2g of water, 0.63g of glacial acetic acid, 0.16g of Ancamine K61B, 1.25g of Aerosol OT75, 0.35g of Schercoquat IAS-PG, 0.05g of 10% Byk-333 in PM glycol ether were also added. Mixing was continued for about 12 hours.
[0063] Example 7 5.62g of polyvinylpyrrolidone K90, 0.09g of Solsperse W100, 75.73g of PM glycol ether were weighed into a container and mixed for 1 hour until a homogeneous mixture was obtained. To this was added 14.74g of the compound obtained in Example 1 with mixing. 1.18g of water, 0.62g of glacial acetic acid, 0.15g of Ancamine K61B, 1.34g of Aerosol OT75, 0.38g of Schercoquat IAS-PG, 0.15g of 1% Tegomer E-Si2330 in PM glycol ether were also added. Mixing was continued for about 12 hours.
[0064] Example 8 8.02g of polyvinylpyrrolidone K90, 0.13g of Solsperse W100, 73.29g of PM glycol ether were weighed into a container and mixed for 1 hour until a homogeneous mixture was obtained. To this was added 14.74g of the compound obtained in Example 1 with mixing. 1.18g of water, 0.62g of glacial acetic acid, 0.15g of Ancamine K61B, 1.34g of Aerosol OT75, 0.38g of Schercoquat IAS-PG, 0.15g of 1% Tegomer E-Si2330 in PM glycol ether were also added. Mixing was continued for about 12 hours.
[0065] Example 94.8g of polyvinylpyrrolidone K90, 0.08g of Solsperse W100, 74.99g of PM glycol ether were weighed into a container and mixed for 1 hour until a homogeneous mixture was obtained. To this was added 16g of the compound obtained in Example 2 with mixing. 1.29g of water, 0.67g of glacial acetic acid, 0.17g of Ancamine K61B, 1.48g of Aerosol OT75, 0.42g of Schercoquat IAS-PG, 0.1g of 1% Tegomer E-Si2330 in PM glycol ether were also added. Mixing was continued for about 12 hours.
[0066] Example 10 4.8g of polyvinylpyrrolidone K90, 0.08g of Solsperse W100, 74.99g of PM glycol ether were weighed into a container and mixed for 1 hour until a homogeneous mixture was obtained. To this was added 16g of the compound obtained in Example 2 with mixing. 1.29g of water, 0.67g of glacial acetic acid, 0.17g of Ancamine K61B, 1.48g of Aerosol OT75, 0.42g of Schercoquat IAS-PG, 0.1g of 10% Byk 333 in PM glycol ether were also added. Mixing was continued for about 12 hours.
[0067] Example 11 6.4g of polyvinylpyrrolidone K90, 0.1g of Solsperse W100, 73.37g of PM glycol ether were weighed into a container and mixed for 1 hour until a homogeneous mixture was obtained. To this was added 16g of the compound obtained in Example 2 with mixing. 1.29g of water, 0.67g of glacial acetic acid, 0.17g of Ancamine K61B, 1.48g of Aerosol OT75, 0.42g of Schercoquat IAS-PG, 0.1g of 10% Byk 333 in PM glycol ether were also added. Mixing was continued for about 12 hours.
[0068] Example 125.59g of polyvinylpyrrolidone K90, 0.08g of Solsperse W100, 74.24g of PM glycol ether were weighed into a container and mixed for 1 hour until a homogeneous mixture was obtained. To this was added 16g of the compound obtained in Example 1A with mixing. 1.28g of water, 0.67g of glacial acetic acid, 0.17g of Ancamine K61B, 1.34g of Aerosol OT75, 0.38g of Schercoquat IAS-PG, 0.02g of 10% Byk 333 in PM glycol ether, 0.23g of 10% Capstone FS61 in PM glycol ether were also added. Mixing was continued for about 12 hours.
[0069] Example 13 3.9g of polyvinylpyrrolidone K90, 0.08g of Solsperse W100, 75.93g of PM glycol ether were weighed into a container and mixed for 1 hour until a homogeneous mixture was obtained. To this was added 16g of the compound obtained in Example 1A with mixing. 1.28g of water, 0.67g of glacial acetic acid, 0.17g of Ancamine K61B, 1.34g of Aerosol OT75, 0.38g of Schercoquat IAS-PG, 0.02g of 10% Byk 333 in PM glycol ether, 0.23g of 10% Capstone FS61 in PM glycol ether were also added. Mixing was continued for about 12 hours.
[0070] Example 14 4.08g of polyvinylpyrrolidone K120, 0.96g of Solsperse W100, 76.02g of PM glycol ether were weighed into a container and mixed for 1 hour until a homogeneous mixture was obtained. To this was added 15.04g of the compound obtained in Example 2 with mixing. 1.2g of water, 0.63g of glacial acetic acid, 0.2g of Ancamine K61B, 1.34g of Aerosol OT75, 0.38g of Schercoquat IAS-PG, 0.15g of 1% Tegomer E-Si2330 in PM glycol ether were also added. Mixing was continued for about 12 hours.
[0071] Example 152 g of polyvinylpyrrolidone K90, 0.08 g of Solsperse W100, 71.47 g of PM glycol ether were weighed into a container and mixed for 1 hour until a homogeneous mixture was obtained. To this was added 22.51 g of the compound obtained in Example 2 with mixing. 1.28 g of water, 0.67 g of glacial acetic acid, 0.17 g of Ancamine K61B, 1.34 g of Aerosol OT75, 0.38 g of Schercoquat IAS-PG, 0.1 g of 1% Tegomer E-Si2330 in PM glycol ether were also added. Mixing was continued for about 12 hours.
[0072] Example 16 4.1 g of polyvinylpyrrolidone K17, 77.28 g of PM glycol ether were weighed into a container and mixed for 1 hour until a homogeneous mixture was obtained. To this was added 14.74 g of the compound obtained in Example 1A with mixing. 1.18 g of water, 0.62 g of glacial acetic acid, 0.17 g of Ancamine K61B, 1.33 g of Aerosol OT75, 0.38 g of Schercoquat IAS-PG, 0.2 g of 10% Byk333 in PM glycol ether were also added. Mixing was continued for about 12 hours.
[0073] Example 17 4.1 g of polyvinylpyrrolidone K90, 0.08 g of Solsperse W430, 77.2 g of PM glycol ether were weighed into a container and mixed for 1 hour until a homogeneous mixture was obtained. To this was added 14.74 g of the compound obtained in Example 1A with mixing. 1.18 g of water, 0.62 g of glacial acetic acid, 0.17 g of Ancamine K61B, 1.33 g of Aerosol OT75, 0.38 g of Schercoquat IAS-PG, 0.2 g of 10% Byk333 in PM glycol ether were also added. Mixing was continued for about 12 hours.
[0074] Example 184.1 g of polyvinylpyrrolidone K90, 0.08 g of Disperbyk 2013, 77.2 g of PM glycol ether were weighed into a container and mixed for 1 hour until a homogeneous mixture was obtained. To this was added 14.74 g of the compound obtained in Example 1A while mixing. 1.18 g of water, 0.62 g of glacial acetic acid, 0.17 g of Ancamine K61B, 1.33 g of Aerosol OT75, 0.38 g of Schercoquat IAS-PG, 0.2 g of 10% Byk333 in PM glycol ether were also added. Mixing was continued for about 12 hours.
[0075] Example 19 4.1 g of polyvinylpyrrolidone K90, 0.08 g of Disperbyk161, 77.2 g of PM glycol ether were weighed into a container and mixed for 1 hour until a homogeneous mixture was obtained. To this was added 14.74 g of the compound obtained in Example 1A while mixing. 1.18 g of water, 0.62 g of glacial acetic acid, 0.17 g of Ancamine K61B, 1.33 g of Aerosol OT75, 0.38 g of Schercoquat IAS-PG, 0.2 g of 10% Byk333 in PM glycol ether were also added. Mixing was continued for about 12 hours. Comparative Example
[0076] Comparative Example 20 4.1g of Polyvinylpyrrolidone K90, 0.08g of Solsperse W100, 77.48g of PM Glycol Ether were weighed into a container and mixed for 1 hour until a uniform mixture was obtained. To this was added 16.35g of Denacol EX-614B with mixing. 0.17g of Ancamine K61B, 1.33g of Aerosol OT75, 0.38g of Schercoquat IAS-PG, 0.11g of 10% Byk333 in PM Glycol Ether were also added. Mixing continued for about 12 hours. This comparative example is similar to Example 3-13, except that it does not contain a urethane resin (it contains only isocyanate-reactive compounds with multiple epoxide functionality, and does not contain an isocyanate).
[0077] Comparative Example 214.9g of polyvinylpyrrolidone K90, 0.08g of Solsperse W100, 76.86g of PM glycol ether were weighed into a container and mixed for 1 hour until a homogenous mixture was obtained. To this was added 12.98g of the compound obtained in Example 1 and 3g of Dencaol EX-830 with mixing. 0.17g of Ancamine K61B, 1.48g of Aerosol OT75, 0.42g of Schercoquat IAS-PG, 0.11g of 10% Byk333 in PM glycol ether were also added. Mixing was continued for about 12 hours. This comparative example is similar to Examples 3-13, except that it contains a smaller amount of urethane resin (less of Example 1 and the addition of the difunctional epoxide Denacol EX-830).
[0078] Comparative Example 22 4.9g of polyvinylpyrrolidone K90, 0.08g of Solsperse W100, 76.86g of PM glycol ether were weighed into a container and mixed for 1 hour until a homogenous mixture was obtained. To this was added 12.98g of the compound obtained in Example 1 and 3g of PEG-600 with mixing. 0.17g of Ancamine K61B, 1.48g of Aerosol OT75, 0.42g of Schercoquat IAS-PG, 0.11g of 10% Byk333 in PM glycol ether were also added. Mixing was continued for about 12 hours. This comparative example is similar to Examples 3-13, except that it contains less urethane resin (less of Example 1 and the addition of PEG-600).
[0079] Comparative Example 2371.55g of PM glycol ether and 24.51g of the compound obtained in Example 1 were weighed into a container and mixed for 30 minutes until a homogenous mixture was obtained. To this was added 1.28g of water, 0.67g of glacial acetic acid and mixed for 1 hour. After 1 hour, 0.17g of Ancamine K61B, 1.34g of Aerosol OT75, 0.38g of Schercoquat IAS-PG, 0.1g of 1% Tegomer E-Si2330 in PM glycol ether were also added. Mixing was continued for about 12 hours. This comparative example is similar to Examples 3-16, except that it does not contain a water-absorbing polymer.
[0080] Comparative Example 24 : A commercially available coating, Visgard Premium SE, from FSI Coating Technologies, was used without further modification.
[0081] Examples 1-19 and Comparative Examples 20-24 were all coated onto the same Gentex polycarbonate lens. All coated parts were prepared in the same manner by dip coating application. The polycarbonate lens (Gentex) was cleaned with soap and water and air dried prior to coating application. After dip coating, the samples were air dried for 1 minute, pre-cured at 90°C for 10 minutes, and cured at 120°C for 2 hours. Test Method
[0082] All tests were performed at room temperature (approximately 18–23°C) unless otherwise indicated.
[0083] Film Thickness: The film thickness of the cured coating was measured using a Filmetrics F20-CP spectrophotometer at a wavelength of 632.8 nanometers (nm) based on spectroscopic reflectance.
[0084] Haze: The light transmittance and light scattering properties of the cured coatings were evaluated by measuring the haze with a Haze-gard Plus (BYK-Gardner, Columbia, MD) haze meter according to the ASTM D 1003 standard.
[0085] Adhesion: Adhesion is the ability of a coating to adhere to a substrate. A roll of Nichiban #405 tape was used to test for initial adhesion. The test was performed as follows: 1) the cured coating was cross-hatched with a 5x5 grid at approximately 2mm intervals using a retractable razor; 2) the tape was pressed firmly (using a tongue depressor) onto the cross-hatched areas; 3) after 90±30 seconds, the tape was pulled at a 180° angle or as close to the substrate as possible; 4) the coated substrate was inspected with an appropriate visual control to check if the coating had been removed; 5) the areas were also inspected microscopically; 6) the actual number of areas that were not affected was reported as percent adhesion (if adhesion was only affected along a line, the rating was converted to a percentage). This test was performed three times. If there was no loss of coating after three pulls, the test was deemed a "pass."
[0086] Initial bonding: When a coated lens is bonded in its original state without any further processing, this is called "initial bonding."
[0087] Boiling Water Adhesion: Coated lenses are placed in boiling water at 100°C for 1 hour. The lenses are removed, air dried overnight, and tested for adhesion as above. This is called "boiling water adhesion."
[0088] High Humidity Adhesion: This is an accelerated test for adhesion of coatings. Coated lenses are placed in a humidity chamber (ESPEC Humidity Cabinet LH-113) at 60°C and 90% relative humidity for 10 days. After 10 days, the samples are equilibrated in room environment for 3-4 hours. The adhesion of the samples is tested as above. The samples are then placed in a water bath at 80°C for 1 hour. After this, the samples are air dried for 3-4 hours and tested for adhesion again. This is called "High Humidity Adhesion - Initial / 80°C, 1 hour".
[0089] K-Mark (Particulate Abrasion Resistance): Particulate abrasion resistance was tested according to EN166 / EN168 protocols. The coated lenses are equilibrated in a desiccator at 20°C and 30% relative humidity for approximately 5 hours. The coated sample is placed in the rotating holder of a Cadex sand drop tester. 3kg of sand is dropped into a funnel 6 feet above the surface of the rotating object. After all 3kg of sand has impacted the surface of the rotating object, the object is removed and washed with soap and water. After washing, the object is blown dry with filtered compressed air. The sample is then placed in a Cadex light diffusion measuring device. To pass this test, the light diffusion must be less than 5cd / m 2* Must be less than lx.
[0090] Coefficient of Friction: The surface smoothness of the cured coating is measured by the coefficient of friction. Cheesecloth (obtained from Summers Optical, meeting MIL CCC-C-440 specifications) is secured to the sled of an Oakland Instruments 7000 Series Film Friction Tester. The sample to be tested is placed coated side down on top of the cheesecloth. A 200g load is applied to the sample and connected to a load cell. The sled is then pulled horizontally away from the load cell, applying friction between the sample and the cheesecloth. The load applied to the coated sample is recorded. The coefficient of friction (COF) is defined as: COF=load cell reading / 200g; the lower the coefficient of friction, the smoother the surface. For reference, Visgard® Premium Plus, a premium commercial product from FSI Coating Technologies, has a measured coefficient of friction of 0.37. A coefficient of friction value of 0.37 is considered "not very smooth / not very smooth," but according to this disclosure, coefficients of friction less than 0.37 are considered smooth or smooth. Unless otherwise stated herein, the coefficient of friction is measured on samples having a polycarbonate substrate.
[0091] Permanence of Slip: The coated samples are immersed in deionized water for 7 hours. The samples are then dried overnight under room conditions. The coefficient of friction is measured on the dried samples. If the coefficient of friction is maintained, the slip is considered "permanent."
[0092] Steel Wool Abrasion: The abrasion / scratch resistance of coated materials when rubbed with standard grade steel wool can be qualitatively determined by measuring the steel wool abrasion with the YT-520 Steel Wool Tester. Japanese steel wool grade 0000 (extra fine) was used for the test. The coated surface was rubbed with the tester for 10 strokes with a 10g weight over an area of approximately 2 inches by 2 inches. The number of scratches on the surface was checked.
[0093] Bag Mark Off Test: A coated lens is placed in an LDPE bag and sandwiched between two uncoated lenses. A 100g weight is then placed on the top lens. The entire setup is placed in a humidity chamber at 30°C and 90% relative humidity for 2 hours. After 2 hours, the test sample is removed from the bag and checked for scratches. Test method - Anti-fog property
[0094] Breath Test: The breath test was performed by holding the coated substrate approximately 2.5-7.5 cm away from the tester, which intentionally blew onto the sample to induce haze. If no haze developed on the coated substrate during the test, the coating composition passed the breath test. If haze appeared on the surface of the coated substrate, the coating composition failed the test.
[0095] Initial Fog Resistance Test: An initial fog resistance test was performed by placing the coated substrate at a standard height (1 inch) above a beaker containing 60°C water. The coated substrate was exposed to water vapor from the 60°C water for 1 minute. If the coated substrate developed fogging during this test, the time until fogging occurred was recorded. If no fogging occurred during the 1 minute exposure, the coating was considered to have "passed" the initial fog resistance test.
[0096] Hand Wipe Anti-Fog Test: Test the coated sample for anti-fog for 10 seconds with 60°C water in a beaker. If no fogging is observed, wipe the sample with a wipe-all tissue moistened with deionized water. After leaving the sample for 1 minute, test again for anti-fog with 60°C water for 10 seconds. If it passes, the sample is considered to have passed in one wipe. Repeat the test in this manner at least 15 times or until the sample fails the anti-fog test.
[0097] Machine Wipe Anti-Fog Test: A lint-free cleanroom wet wiper is moistened and attached to a steel wool tester (YT-520 Steel Wool Tester). A 100g weight is loaded onto the tester. The coated lens is placed on the tester and wiped with 5 strokes. The coated sample is then left for 1 minute and tested for anti-fog with 60°C water for 10 seconds. No fogging is a "pass" in one cycle. The test sample is left for 3 minutes and then re-examined. The test is run for 10 cycles or until the sample fails the anti-fog test.
[0098] Water Immersion Anti-Fog Test: The coated substrate was immersed in water at room temperature for 1 hour. The coated specimen was then removed from the water and hung on a rack at 25°C and 50% relative humidity for 12 hours, and the anti-fogging properties were tested by placing the coated substrate over a beaker of water at 50°C for 3 minutes. If fogging occurred on the coated substrate during this test, the time it took for fogging to occur was recorded. If no fogging occurred during the 1 minute exposure, the coating was considered to have "passed" the 1 hour water immersion anti-fogging test.
[0099] N-Mark Anti-Fog Test: Additionally, the coated specimens immersed in water for 12 hours were tested for anti-fogging using a YT-810 anti-fogging tester (Yin Chung Co., Ltd.) according to EN166 / EN168 protocols. This procedure constitutes the N-Mark test. In the test, the coated substrate is placed on the tester. To start the test, the coated substrate is exposed to steam at 50°C and a laser is irradiated through the lens. The amount of fogging was determined by the decrease in laser light transmittance during 8 seconds of irradiation. If the laser light transmittance falls below 80% of the initial value during the 8 seconds, the coating fails the fogging test, otherwise it is rated as passing.
[0100] 2-hour water immersion N-mark anti-fog test: The coated substrate was immersed in water at room temperature for 2 hours. The coated specimen was then removed from the water and hung on a rack at 25°C and 50% relative humidity for 12-24 hours, and tested for anti-fog properties using a YT-810 anti-fog tester (manufactured by Ying Chung Co., Ltd.) according to the ISO 18526-3:2020 protocol. This procedure constitutes the 2-hour water immersion N-mark anti-fog test. In this test, the coated substrate is placed on top of the YT-810 tester. When the test begins, the coated substrate is exposed to steam at 50°C and a laser is irradiated through the lens. The amount of fogging was determined by the decrease in laser light transmittance in 8 seconds of irradiation. If the laser light transmittance falls below 80% of the initial value in 8 seconds, the coating fails the fogging test, otherwise it is rated as passing.
[0101] Frost Resistance Test: Place the sample in a -18°C freezer for 1 hour. After 1 hour, remove the sample to ambient conditions (20±5°C, 30-50% relative humidity). Observe the coated area for 1 minute. If no frost is observed, the coating passes the frost resistance test.
[0102] The measured characteristics of the examples are shown in Tables 1 to 3. [Table 2] [Table 3] [Table 4]
[0103] Examples 3-8 were prepared using a siloxane-containing urethane epoxide resin, and Examples 9-11 were prepared using a non-silicon-containing urethane epoxide resin. Examples 3-8 showed relatively higher abrasion resistance than Examples 9-11, possibly due to the silicone component improving the abrasion resistance of the coating.
[0104] Examples 3 to 15 pass the boiling water adhesion test (treatment with boiling water at 100°C for 1 hour). On the other hand, Examples 16 to 19 have a low isocyanate content in the urethane resin and fail the boiling water adhesion test. The effect of isocyanate is further illustrated in Comparative Example 20, which does not contain isocyanate (and therefore does not contain urethane resin).
[0105] The results of Comparative Examples 21 and 22 show that the epoxide component also plays a role in adhesion. Both have the same amount of urethane resin component, but Comparative Example 21 contains an additional epoxide component (Denacol EX-830, a difunctional epoxide), whereas Comparative Example 22 contains PEG-600 (polyethylene glycol 600) instead. Comparative Example 21 shows better adhesion than Comparative Example 22.
[0106] The bag mark-off test is important to evaluate the suitability for multi-packing solutions. Comparative Example 24 leaves scratches on the LDPE bag when packed in the bag. In contrast, Examples 3-11 do not leave scratches on the bag when packed in the LDPE bag. Also, Examples 3-11 have a low coefficient of friction and a smooth surface feel.
[0107] All the tested examples passed the initial anti-fogging test. Furthermore, Examples 5 to 13 passed the water immersion anti-fogging test (treatment by immersing in water for 1 hour). Examples 5 to 13 are considered to contain an appropriate amount of water-absorbing polymer (polyvinylpyrrolidone K90) (in the range of 17.9 to 32.56 wt % based on the total solids) and urethane resin (in the range of 59.8 to 73.43 wt % based on the total solids). Examples 3, 4, and 15 and Comparative Example 23 have a low or zero amount of polyvinylpyrrolidone K90 and fail the water immersion anti-fogging test. Examples 14 and 16 contain polyvinylpyrrolidone K120 with a molecular weight of 3 million daltons and polyvinylpyrrolidone K17 with a molecular weight of 16,000 daltons, respectively, as water-absorbing polymers. Both Examples 14 and 16 showed poor results in the water immersion anti-fogging test. Comparative Example 20 does not contain urethane resin. Comparative Examples 21 and 22 contain urethane resins formed from different components compared to the other Examples. Each of Comparative Examples 20 to 22 failed the water immersion anti-fogging test, which indicates that the properties of the urethane resin are also important for passing the water immersion anti-fogging test.
[0108] Table 4 contains the test results for durability of surface slippage for Example 4. [Table 5]
[0109] Although the present disclosure describes exemplary embodiments of compositions, articles, and methods in detail, the disclosure is not intended to be limited to the disclosed embodiments, and specific elements of the exemplary embodiments disclosed herein are not limited to any exemplary embodiment, but instead apply to all embodiments of the present disclosure.
[0110] The terms defined herein are only for describing aspects of the present disclosure and should not be construed as limiting the entire disclosure. All references to singular features or limitations in this disclosure shall include the corresponding plural features or limitations, and vice versa, unless otherwise specified or clearly implied to the contrary by the context in which the reference is made. Unless otherwise specified, "a", "an", "the", and "at least one" are used interchangeably. Furthermore, as used in this specification and the appended claims, the singular forms "a", "an", and "the" include these plural forms unless the context clearly indicates otherwise.
[0111] To the extent that the term "comprises" or "comprising" is used in the specification or claims, it is intended to be inclusive in the same manner as the term "comprises" is interpreted when used as a transitional word in the claims. Furthermore, when the term "or" is used (e.g., A or B), it is intended to mean "A or B, or both." If the applicant intends "only A or B, but not both," the term "only A or B, but not both" is used. Thus, the use of the term "or" herein is inclusive and not exclusive. Furthermore, the phrase "at least one of A, B, and C" should be interpreted as "only A, or only B, or only C, or any combination thereof."
[0112] The multi-component compositions and related methods of the present disclosure may comprise, consist of, or consist essentially of the essential elements of the present disclosure described herein, as well as any additional or optional elements described herein or that are otherwise useful in the preparation and application of hybrid epoxy resins.
[0113] All percentages, parts and ratios used herein are by weight of the total composition unless otherwise specified. All ranges and parameters disclosed herein, including but not limited to percentages, parts and ratios, are understood to include all subranges envisioned and encompassed therein, and all numbers between the endpoints. For example, a range described as "1-10" should be considered to include all subranges beginning with a minimum value of 1 or more and ending with a maximum value of 10 or less (e.g., 1-6.1, or 2.3-9.4), and each integer contained within that range (1, 2, 3, 4, 5, 6, 7, 8, 9, and 10).
[0114] Any combination of method or process steps used herein may be performed in any order unless otherwise specified or unless the contrary is clearly implied by the context in which the referenced combination is made.
Claims
1. a. urethane resins obtained by reacting isocyanate-reactive compounds having multiple epoxide functionality with isocyanates; b. a water-absorbing polymer, and c. a hardener; d. Solvent A coating composition comprising: A coating composition which, when applied to a substrate and heat cured, forms a clear, smooth coating with durable anti-fog properties.
2. 10. The coating composition of claim 1, wherein when the coated substrate is immersed in water for 1 hour, equilibrated at 25°C and 50% relative humidity for at least 12 hours, and tested for anti-fog properties with water at 50°C, no fogging is present for at least 8 seconds.
3. 10. The coating composition of claim 1, wherein when the coated substrate is immersed in water for 2 hours, equilibrated at 25°C and 50% relative humidity for at least 12 hours, and tested for anti-fog properties with water at 50°C, no fogging is present for at least 8 seconds.
4. The coating composition of any one of claims 1 to 3, wherein the coating has a coefficient of friction of less than 0.
37.
5. The coating composition of any one of claims 1 to 4, wherein the isocyanate-reactive compound having multi-epoxide functionality contains at least one hydroxyl group.
6. The coating composition of any one of claims 1 to 5, wherein the isocyanate-reactive compound having multi-epoxide functionality is ethoxylated.
7. The coating composition of any one of claims 1 to 6, wherein the isocyanate-reactive compound having multi-epoxide functionality is silicon-free.
8. 8. The coating composition of claim 7, wherein the silicon-free isocyanate-reactive compound having multi-epoxide functionality contains three or more epoxide groups.
9. The isocyanate-reactive compound having multiple epoxide functionality is selected from the group consisting of aliphatic polyepoxides, glycerol polyglycidyl ethers, polyglycerol polyglycidyl ethers, sorbitol polyglycidyl ethers, ethylene glycol diglycidyl ethers, diethylene glycol diglycidyl ethers, polyethylene glycol diglycidyl ethers, polypropylene glycol diglycidyl ethers, phenoxy(ethylene oxide) 5 Glycidyl ether, and lauryloxy (ethylene oxide) 15 9. The coating composition of claim 1, wherein the glycidyl ether or combination thereof is selected from the group consisting of glycidyl ethers, glycidyl ethers, and combinations thereof.
10. The coating composition of any one of claims 1 to 9, wherein the isocyanate comprises at least one silicon-containing isocyanate.
11. 11. The coating composition of claim 10, wherein the at least one silicon-containing isocyanate is a reactive isocyanate alkoxysilane.
12. The at least one silicon-containing isocyanate is NCO(R)Si(OR 1 ) 3 , NCO(R)Si(OR 1 ) 2 R 3 , NCO(R)Si(OR 1 ) (R 3 ) 2 (R = (CH 2 ) n , n=1 to 6, R 1 =CH 3 Or C 2 H 5 , and R 3 = C x H 2x+1 11. The coating composition of claim 10, having the general structure:
13. 12. The coating composition of claim 11, wherein the urethane resin containing alkoxysilane groups is further hydrolyzed.
14. The coating composition of any one of claims 10 to 13, wherein the isocyanate further comprises at least one non-silicon containing isocyanate.
15. The coating composition of any one of claims 1 to 9, wherein the isocyanate is silicon-free.
16. The coating composition of any one of claims 1 to 11, wherein the isocyanate has an isocyanate functionality greater than 1.
17. 17. The coating composition of claim 16, wherein the isocyanate is selected from isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), xylene diisocyanate (XDI), toluene diisocyanate (TDI), diphenylmethane diisocyanate, HDI biuret, diisocyanates derived from the isocyanates, or combinations thereof.
18. 18. The coating composition of any one of claims 1 to 17, wherein the water-absorbing polymer is selected from polyvinylpyrrolidone, poly(vinylpyrrolidone-co-vinyl acetate), poly(vinylpyrrolidone-co-ethyl acrylate), poly(vinylpyrrolidone-co-vinyl chloride), polyvinyl alcohol, sulfonic acid esters, polyacrylic acid, or combinations thereof.
19. The coating composition of any one of claims 1 to 18, wherein the curing agent is an amine, an amine salt, or a combination thereof.
20. The coating composition of any one of claims 1 to 19, further comprising a polymeric dispersant having hydrophilic and hydrophobic segments.
21. The coating composition of any one of claims 1 to 20, further comprising a non-reactive surfactant.
22. 22. The coating composition of any one of claims 1 to 21, wherein no frost forms on the coating when a substrate formed with the coating is placed at -18°C for 1 hour and then at 20±5°C and a relative humidity of 30 to 50%.
23. 23. The coating composition of any one of claims 1 to 22, wherein the coating does not form a haze while the substrate formed thereon is exposed to water vapor at 60°C for 10 seconds after wiping the substrate with a lint-free cleanroom wet wiper for 10 cycles with 5 strokes of 100g weight in each cycle.
24. 24. The coating composition according to any one of the preceding claims, wherein the coating passes the K-mark (abrasion resistance to fine particles) test according to the EN166 / EN168 protocols.
25. 25. The coating composition of any one of claims 1 to 24, wherein the coefficient of friction of the coating is maintained between 0.1 and 0.37 after immersion in deionized water for 7 hours.
26. The coating composition of any one of claims 1 to 25, wherein the coating is suitable for anti-reflective or mirror coating.
27. a. urethane resins obtained by reacting isocyanate-reactive compounds having multiple epoxide functionality with isocyanates; b. a water-absorbing polymer; c. a hardener; d. a solvent, and e. Dispersant 1. A coating composition comprising:
28. 30. The coating composition of claim 27, wherein when applied to a substrate and thermally cured, the coating composition forms a clear, smooth coating having durable anti-fog and / or anti-frost properties.
29. An article having a substrate and a transparent, smooth and permanent anti-fog coating disposed on the substrate, the coating is formed from a coating composition including a urethane resin, a water-absorbing polymer, a curing agent, a dispersant, and a solvent; The article wherein the urethane resin is the reaction product of an isocyanate-reactive compound having multiple epoxide functionality and an isocyanate.
30. 30. The article of claim 29, wherein when the coated substrate is immersed in water for 1 hour, equilibrated at 25°C and 50% relative humidity for at least 12 hours, and tested for anti-fog properties with water at 50°C, no fogging is present for at least 8 seconds.
31. 30. The article of claim 29, wherein when the coated substrate is immersed in water for 2 hours, equilibrated at 25°C and 50% relative humidity for at least 12 hours, and tested for anti-fog properties with water at 50°C, no fogging is present for at least 8 seconds.
32. The article of any one of claims 29 to 31, wherein the coating has a coefficient of friction of less than 0.
37.
33. 33. The article of any one of claims 29 to 32, wherein no frost forms on the coating when the coated substrate is placed at -18°C for 1 hour and then at 20±5°C and 30-50% relative humidity.
Citation Information
Patent Citations
Flame-retarding waterproof antibacterial board paint
CN105086551A
Anti-fogging coating liquid and coated article
JP2006225614A
Anti-fogging coating liquid and antifogging goods
JP2008007677A
Coating agent, and laminated sheet and molded article using the same
JP2019094422A
Anti-Fogging Coating Solution and Anti-Fogging Article
US20080207797A1